A transcriptomic view of the proteome variability of newborn and adult Bothrops jararaca snake venoms. - André Zelanis; Débora Andrade-Silva; Marisa M Rocha; Maria F Furtado; Solange M T Serrano; Inácio L M Junqueira-; Paulo Lee Ho (Public Library of Science (PLoS), 2012)
BACKGROUND: Snake bite is a neglected public health problem in communities in rural areas of several countries. Bothrops jararaca causes many snake bites in Brazil and previous studies have demonstrated that the pharmacological activities displayed by its venom undergo a significant ontogenetic shift. Similarly, the venom proteome of B. jararaca exhibits a considerable variation upon neonate to adult transition, which is associated with changes in diet from ectothermic prey in early life to endothermic prey in adulthood. Moreover, it has been shown that the Brazilian commercial antibothropic antivenom, which is produced by immunization with adult venom, is less effective in neutralizing newborn venom effects. On the other hand, venom gland transcripts of newborn snakes are poorly known since all transcriptomic studies have been carried out using mRNA from adult specimens. METHODS/PRINCIPAL FINDINGS: Here we analyzed venom gland cDNA libraries of newborn and adult B. jararaca in order to evaluate whether the variability demonstrated for its venom proteome and pharmacological activities was correlated with differences in the structure of toxin transcripts. The analysis revealed that the variability in B. jararaca venom gland transcriptomes is quantitative, as illustrated by the very high content of metalloproteinases in the newborn venom glands. Moreover, the variability is also characterized by the structural diversity of SVMP precursors found in newborn and adult transcriptomes. In the adult transcriptome, however, the content of metalloproteinase precursors considerably diminishes and the number of transcripts of serine proteinases, C-type lectins and bradykinin-potentiating peptides increase. Moreover, the comparison of the content of ESTs encoding toxins in adult male and female venom glands showed some gender-related differences. CONCLUSIONS/SIGNIFICANCE: We demonstrate a substantial shift in toxin transcripts upon snake development and a marked decrease in the metalloproteinase P-III/P-I class ratio which are correlated with changes in the venom proteome complexity and pharmacological activities.